Selective extraction of Am(III) from PUREX raffinate: the AmSel System - Wagner, Christoph; Müllich, Udo; Geist, Andreas; Panak, Petra (Solvent extraction and ion exchange, 2016)
The separation of actinides(III) from used nuclear fuel is a key step for the recycling of used nuclear fuel in innovative fuel cycles. However, high neutron dose rates and heat load of short-lived curium isotopes complicate the production and handling of new nuclear fuel containing curium(III) and americium(III). Therefore, new processes have to be developed separating only americium(III) from PUREX (Plutonium-Uranium Recovery by Extraction) raffinate. This is achieved by coextracting An(III) and Ln(III) from PUREX raffinate using N,N,N’,N’-tetraoctyl-diglycolamide (TODGA), followed by the subsequent selective stripping of Am(III) by a water-soluble bis-triazinyl-bipyridin (sodium 3,3’,3’’,3’’’-([2,2’-bipyridine]-6,6’-diylbis(1,2,4-triazine-3,5,6-triyl))tetrabenzenesulfonate, SO3-Ph-BTBP). The selectivity for Am(III) over Cm(III) is SFCm(III)/Am(III) ≈ 2.5, due to the inverse selectivity of TODGA and SO3-Ph-BTBP. Additionally, a separation factor up to 1200 is achieved for the separation of Eu(III) from Am(III). The results demonstrate that the presented system works very well even at acidic conditions using nitric acid as the aqueous phase and does not require additional salting out agents.